PERSEPSI GURU DAN DOSEN DI KOTA SEMARANG TENTANG TUNJANGAN PROFESI GURU DAN DOSEN - Aziz Pilar Syefiaji; Sri Suwitri; Margaretha Suryaningsih (Journal of Public Policy and Management Review, 2015)
Welfare conditions of teachers and lecturers in Indonesia is one of the lowest in the world. When compared with neighboring countries, the salary of teachers in Indonesia is still relatively low compared to Malaysia, Thailand and Singapore. That condition is one of the causes of the poor quality of education in Indonesia. Based on data from The Learning Curve Pearson 2014, a rating agency's education, explained that Indonesia ranks 40th out of 40 countries with an index ranking and overall value that is minus 1.84. In order to improve the welfare of teachers and to improve the quality of education in Indonesia is carried out allowances and lecturers teaching profession. However, in the implementation of the policy there are still many problems. The purpose of research is to determine how perceptions of teachers and lecturers in Semarang on professional allowances of teachers and lecturers as well as the role of aspects of the experience and motivation of teachers and lecturers in shaping the perception of teachers and lecturers in Semarang on professional allowance for teachers and lecturers. Researchers used qualitative descriptive research methods. The results showed that the perception of teachers and lecturers in Semarang on professional allowances of teachers and lecturers are positive perception. Aspects of the experience and motivation of teachers and lecturers role in shaping perceptions about the benefits of teachers and lecturers and professors teaching profession. From this research can also be seen that in the implementation of professional allowance for teachers and lecturers there are problems such as late payment of professional allowance for teachers and lecturers.